ANALYSIS OF CONSUMER LOYALTY FOR MUD CRABS (SCYLLA SERRATA) AT SEMBAM FISH MAROLA RESTAURANTS IN BENGKULU CITY - Ahdiati, Laila; Cahyadinata, Indra; Sumantri, Bambang (Journal of Agri Socio Economics and Business, 2024)
Mud crab is a type of crab that is very popular with seafood lovers because its meat is delicious and rich in nutrients. In the culinary business, business owners offer various dishes that rely on mud crab as the main ingredient, such as crab in sauce, crab in Padang sauce, pindang crab, crab soup, and so on. This research aims to determine the extent of consumer loyalty towards processed mud crab at the Sembam Ikan Marola Restaurant in Bengkulu City. The method used was purposive sampling with the criteria of consumers who had made purchases at least twice, and data collection was carried out through a questionnaire involving 96 respondents. Measurement analysis uses the consumer loyalty pyramid method. The results of the research show that the inverted pyramid shape means that consumer loyalty at the Sembam Fish Marola Mangrove Crab restaurant has formed strong brand equity. This type of consumer loyalty falls into the "Like the product" category with a value of 69%, which shows that consumers who buy processed mud crab are those who really like processed mud crab.